Research progress of BK virus and systemic lupus erythematosus - Zhao, Jiawei; You, Xin; Zeng, Xiaofeng (Lupus, 2022)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease in which patients are often infected by viruses due to deficient immunity or immunosuppressant use. BK virus (BKV)mainly affects the kidney and can also cause multiple organ involvement throughout the body, which is similar to SLE. BKV is mostly a latent infection in vivo. The incidence of virus reactivation is higher in SLE patients. Reactivation of BKV can induce the production of autoantibodies, thereby promoting the occurrence and development of SLE. Purpose: Aim of this article is to review the prevalence and pathegenesis of BKV infection in SLE patients. Method: The literature search was conducted using four different databases including PubMed, Cochrane Library, Scopus and Web of Science. Results: BK virus is higher infection and reactivation in SLE patients. The "hapten carrier" mechanism may lead to the production of autoantibodies. Some immunosuppressive drugs, like leflumide and hydroxychloroquine, may show a protective effect. Conclusions: BKV infection plays a role in the occurrence and development of SLE, and its significance deserves further exploration.